2002
DOI: 10.2337/diabetes.51.12.3577
|View full text |Cite|
|
Sign up to set email alerts
|

Cellular Basis of Diabetic Nephropathy

Abstract: Transforming growth factor-␤ (TGF-␤) may be critical in the development of diabetic nephropathy (DN), and genetic predisposition is an important determinant of DN risk. We evaluated mRNA expression levels of TGF-␤ system components in cultured skin fibroblasts (SFs) from type 1 diabetic patients with fast versus slow development of DN. A total of 125 long-standing type 1 diabetic patients were ranked by renal mesangial expansion score (MES) based on renal biopsy findings and diabetes duration. Patients in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 26 publications
2
62
0
2
Order By: Relevance
“…We also demonstrated that the upregulation of Tgfb expression and protein levels in diabetic kidneys were markedly inhibited in BNP-Tg mice (Figs 3, 4). Considering a pathogenic role for TGF-β in cellular dysfunction, fibrogenesis and glomerular hypertrophy in diabetes [3,28,35], it is conceivable that the inhibition of renal TGF-β system activation contributed significantly to the observed protective effects of BNP from diabetic renal injury. Although the effect of BNP on glomerular haemodynamics was not investigated, it may be possible that the chronic excess of BNP lessened glomerular hypertension by inhibiting the RAS and TGF-β system tonically.…”
Section: Discussionmentioning
confidence: 99%
“…We also demonstrated that the upregulation of Tgfb expression and protein levels in diabetic kidneys were markedly inhibited in BNP-Tg mice (Figs 3, 4). Considering a pathogenic role for TGF-β in cellular dysfunction, fibrogenesis and glomerular hypertrophy in diabetes [3,28,35], it is conceivable that the inhibition of renal TGF-β system activation contributed significantly to the observed protective effects of BNP from diabetic renal injury. Although the effect of BNP on glomerular haemodynamics was not investigated, it may be possible that the chronic excess of BNP lessened glomerular hypertension by inhibiting the RAS and TGF-β system tonically.…”
Section: Discussionmentioning
confidence: 99%
“…The primers for the EMT-and MET-associated genes (Table 5) were designed using Oligo6 (Molecular Biology Insights, Cascade, CO) or PRIMER3 32 or obtained from peer-reviewed articles. 33,34 For primer design, the mRNA gene sequences were obtained from GenBank, 35,36 and exact full-sequence alignment was validated by BLASTN. 37 QRT-PCR was performed on all samples used on the arrays, including those that were inadequate for the arrays (n ϭ 55), using SYBR Green I detection system with heat-activated Taq DNA polymerase and uracil DNA glycosylase (Platinum SYBR Green qPCR SuperMix-UDG; Invitrogen).…”
Section: Quantitative Reverse Transcriptase Pcrmentioning
confidence: 99%
“…[16] Symptoms Blurred vision, polyurea, polyphagia, polydipsia, weight loss, constipation, cramps, thirst, hunger, weakness, [17,18] and candidiasis are common symptoms for both type-1 and type-2 DM. [1] Apart from that the patients with Type-1 DM have both microvascular problems [5][6][7][8][9][10] and macrovascular diseases such as heart, peripheral vascular and coronary artery diseases [11,12] while patients with Type 2 DM have high risk of large vessel atherosclerosis commonly associated with obesity, hypertension, hyperlipidaemia. [11,12,19,20] Most patients are die with type-2 diabetes due to cardiovascular complications and end stage renal disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Deficiency of insulin leads to chronic hyperglycemia with disturbances of fat, protein and carbohydrate metabolism. [1][2][3][4] Long term diabetes cause tissue or vascular damage and leads some dangerous complications like neuropathy [5,6] , nephropathy [7,8] , retinopathy [9,10] , cardiovascular complications [11,12] and ulceration. [13,14] First diabetic classification and diagnostic criteria was given by World Health…”
Section: Introductionmentioning
confidence: 99%